Why scientists agree to participate in science festivals: evidence from South Africa. Issue 2 (3rd April 2021) - Gavhi-Molefe, Mpfareleni Rejoyce; Jensen, Eric; Joubert, Marina
ABSTRACT: Scientists are key actors in public engagement activities, such as science festivals. This study sought to explore factors that encouraged and/or deterred scientists' participation in Scifest Africa, the flagship science festival in South Africa. A self-administered, online survey was completed by 40 scientists who participated in this science festival in 2019. The survey was comprised of a mix of closed- and open-ended questions, and responses were processed statistically and thematically. The results showed that objectives of informing, exciting and inspiring the public were key motivators, while time constraints and concerns over the efficacy of engagement were prominent deterrents. Factors linked to the legacy of apartheid in South Africa and current societal challenges, inspired a strong moral obligation amongst most scientists to give something back to society through inclusive platforms such as the Scifest. In particular, for black African and/or female scientists, being role models was a key motivating factor. Our findings illustrate the importance of context-specific factors concerning motivators for public engagement. Understanding why scientists participate in public engagement events, is crucial for festival organisers, who rely on scientists as volunteers. These insights could also help to advance public engagement with science, which features prominently in government policy frameworks.